Resolução de Sistemas de Equações Lineares: Álgebra e Geometria - Cunha, Laeny Layara Pereira (2021)
The main objective of this work is the study of linear systems for high school, including geometric interpretations. Cramer's Rule appears naturally, in systems of two equations and two unknowns, and from that point onwards, the extension was made to systems with $3$ equations and $3$ unknowns. The results were proved in an elementary way without using more advanced techniques on matrices and determinants. We finish with the scaling method to solve general linear systems.